Marketization allocation, land price, and local government land speculation, China - Zhang, Juanfeng; Yu, Ting; Li, Lele; Zhang, Danxia; Zhao, Guochao; Wen, Haizhen (International Journal of Strategic Property Management, 2020)
Land value appreciation in the urbanization process has triggered market speculation. The Land Bank System strengthens local governments’ ability to control land supply and distribution rights. Local governments are considered close stakeholders. Under the pressure of guaranteeing economic growth and promotion, local governments have increased their dependence on land finances. It is important for investors to understand the local governments’ behaviors, and draw up business strategies. This study aims to examine the influencing factors and formation mechanism of local government land hoarding. The research hypothesis was tested by collating provincial-level panel data of China from 2004 to 2015 and using dynamic panel data estimated by the Generalized Method of Moments (GMM). A significant positive correlation was found between residential land price and land hoarding area by local governments. Land speculation in the eastern region is also more pronounced than that in central and western regions. In addition, empirical studies have found a correlation between the degree of government intervention and local government land hoarding behavior. The higher the degree of government intervention, the less land sold through bid invitation, auction, and listing, which are linked to the corresponding hoarding land area.